Epileptic-like activity in cultured neuronal circuits : effects on synapsin suppression = Actividad epileptiforme en circuitos neuronales en cultivo : efectos de la supresión de la sinapsina - Brenes García, Oscar Gerardo 1982-; Montarolo, Pier Giorgio; Romero Vásquez, Adarli ([San José], C.R., 2016)
Synapsins (Syns) are an evolutionarily conserved family of synaptic vesicle-associated proteins crucial for the fine-tuning of synaptic function. Studies with marnmals have partially clarified the different roles of Syns. However, the presence of different genes and isoforms and the development of compensatory mechanisms hinder accurate data interpretation. A variety of reports have linked Syns with the development of epilepsy in humans and animal models. The main mechanism proposed in based on the Syn-mediated imbalance in networks toward hyperexcitability due to differential effects on excitatory and inhibitory synapses. However, possible Syn effects in single neurons and isolated monosynaptic circuits in absence of synaptic inputs must be tested. Here, we used Helix neurons as a reliable experimental model to investigate the effects of Syn knock-down in single cells and monosynaptic circuits. Neurons overexpressing an antisense construct against Helix Syn showed a time-dependent decrease of Syn immunostaining, confirming protein loss. At the morphological leve!, Syn-silenced neurons showed a reduction in neurite linear outgrowth and branching and in the size and the number of synaptic varicosities. Functionally, Syn-silenced neurons presented a reduced ability to form synaptic connections; however, functional chemical synapses showed similar basal excitatory postsynaptic potentials and similar short-term plasticity paradigms with respect to control neurons. In addition, Syn-silenced neurons presented faster neurotransrnitter release and decreased postsynaptic response toward the end of long tetanic presynaptic stimulations. Probably related with an increased readily releasable pool and a compromised reserve pool. We also found that Syn silencing increases cell excitability, characterized by a slightly depolarized resting membrane potential, decreased rheobase, reduced threshold for action...
Tesis (doctorado académico en ciencias)--Universidad de Costa Rica. Sistema de Estudios de Posgrado, 2016
Resumen es español
Keywords: EPILEPSIA; RED NERVIOSA; NEURONAS; SINAPSINAS; SINAPSIS; CULTIVO DE CELULAS